On the Appearance of Elastoplastic Pulses Generatedby Pulsed Beams of Charged Particles on the Back Surfaceof a Metallic Target; Russian Metallurgy (Metally); Vol. 2001, № 3 - Boyko (Boiko) V. I. Vladimir Ilyich (2001, 2001)
Title screen